1998
DOI: 10.1177/004051759806800706
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Flame Retardation and Phase Transition Behavior of Polyester Fabrics Treated with a Bromine-Containing Compound

Abstract: Poly (ethylene terephthalate) (PET) fabrics are treated with meso-1,2,3,4-tetrabromobutane (TBB) to investigate flame retardation. The limiting oxygen index (LOI) value increases with an increasing amount of absorbed TBB (A TBB ) and reaches 28.1 % when A TBB is 10.20% owf. The slope of LOI is 1.14%/% owf from 0 to 4.65% owf of A TBB , and the slope decreases 0.31%/% owf at a region higher than 4.65% owf. The phase transition behavior of treated samples, investigated with differential scanning calorimetry, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Kubokawa and Hatakeyama32 treated PET fabrics with meso ‐1,2,3,4‐tetrabromobutane which was absorbed by the fibers. It was found that the OI values increase with increasing amount of absorbed flame retardant and reaches 28 when the fibers absorb a maximum of 10.2 wt%.…”
Section: Halogen‐containing Flame Retardantsmentioning
confidence: 99%
“…Kubokawa and Hatakeyama32 treated PET fabrics with meso ‐1,2,3,4‐tetrabromobutane which was absorbed by the fibers. It was found that the OI values increase with increasing amount of absorbed flame retardant and reaches 28 when the fibers absorb a maximum of 10.2 wt%.…”
Section: Halogen‐containing Flame Retardantsmentioning
confidence: 99%
“…4,5 Halogen-containing compounds were once used as effective flame retardants for PET, which were forbidden due to the environmental issues. 6,7 Phosphorus-containing flame retardants were considered as one of the most effective alternatives which have been studied for the flame-retardant treatment of PET. 8,9 Especially, the phosphorus-containing flame retardants which could act through forming carbonaceous protective layers have been proven to be effective for the inhibition of melt dripping.…”
Section: Introductionmentioning
confidence: 99%
“…For isothermal measurements at 380 or 422°C, Fig- containing 10.20% owf TBB with those of the untreated fabric. When a sample was continuously heated in an electric furnace for isothermal measurements, it took [3][4][5] minutes to reach the desired temperature. After arriving at the desired temperatures, sample temperatures were approximately constant.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous paper [4], we studied the relationship between flame retardation and the phase transition behavior of poly ( ethylene terephthalate ) ( PET ) fabrics treated with a bromine-containing flame retardant, me.so-1,2,3,4-tetrabromobutane (TBB), using differential scanning calorimetry. Our work revealed that the depression of the melting initial temperature is directly proportional to the effect of flame retardation.…”
mentioning
confidence: 99%